Características das panículas e viabilidade de cariopses de cana-de-açúcar (Saccharum spp.) - Nunes, Mônica Franco (2020)
In sugarcane genetic improvement programs, it is essential to perform crosses that produce viable caryopses to provide seedlings used in the selection process for new varieties. The objective of this study was to evaluate the physical characteristics of panicles and caryopses, and the physiological quality of caryopses in function of the cleaning method, position in the panicle, size of caryopses, year of crossing and, to establish classes of embryonic damage through the tetrazolium. Panicles of fifteen genotypes were obtained from crosses of the multiple parental type or free pollination in the years 2017 and 2018. Caryopses harvested from the upper, middle and lower third of the panicles were evaluated and, when subjected to the mechanical cleaning method, they were classified according to size, into large and small. Regarding physical characteristics, masses of fuzz and caryopses, number of caryopses per position, water content, width and length of caryopses were evaluated. The physiological quality was evaluated first by the percentage and germination speed index.After stabilizing germination, caryopses that did not germinate were subjected to the tetrazolium test, evaluating the presence and location of damage in the embryo (coleoptyl, plumule, mesocotyl, radicle, coleorriza and scutellum), grouping them into eleven damage classes. To validate the methodology of the tetrazolium test, analyzes were carried out with the genotypes LJ10, RB016916 and RB92579, comparing the germination potential and the incidence of embryonic damage between dried or not dried caryopses with the traditional germination test evaluation of the tetrazolium test. The data obtained in the evaluations were analyzed according to a completely randomized design, in a double or triple factorial scheme, using the software R. To compare the means, the Tukey test (5%) was used. As for the variables fuzz mass, mass of caries and number of caries in function of the position in the panicles, in the average of the genotypes the best results were obtained when the caries developed in the middle third of the panicles. Carypses in the lower third showed higher water content compared to karypses in the other positions. In general, the width of the caryopses did not differ between the panicle positions. Embryonic structures, when injured, make it impossible for sugarcane caryopses to germinate. Of the eleven established classes, ten refer to non-viable caryopses.The classes of embryonic damage vary according to the year, genotype, position and size of the caryopsis. The different methodologies of the tetrazolium test make it possible to evaluate the physiological characteristics of the embryo of sugarcane caryopses. Embryonic damage does not come from the mechanical cleaning process. Caryopses in the middle and upper thirds had a higher GVI when compared to the lower third of the panicles in 2017. Caryopses in the middle and upper thirds had a higher GVI when compared to the lower third of the panicles in 2017. A higher percentage of germination was obtained by evaluating the caryopses classified as large. The year of production interferes with the germination of sugarcane caryopses.